Spectroscopic method for measuring intensity of built-in electric field on surface of gallium nitride crystal
Through the ultrafast transient reflection spectroscopy method, the built-in electric field intensity of the gallium nitride crystal surface is successfully measured using pump-detection technology and carrier diffusion-drift coupling model, solving the problem of difficult measurement in the existing technology and achieving efficient and non-invasive measurement effects.
Patent Information
- Application Number
- CN202411721418.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-11-28
AI Technical Summary
The prior art is difficult to effectively measure the built-in electric field strength of the gallium nitride crystal surface, which affects the understanding and optimization of semiconductor device performance.
The ultrafast transient reflection spectroscopy method is used to change the pump light wavelength and regulate the initial carrier concentration distribution through pump-detection technology. The detection light is used to monitor the evolution of reflectivity in real time, and fit the carrier diffusion-drift coupling model to obtain the intensity of the built-in electric field.
The non-invasive measurement of the built-in electric field strength of the gallium nitride crystal surface without contacting the sample provides high spatial resolution measurements suitable for studying fragile or difficult-to-treat semiconductor materials.
Smart Images

Figure CN119643985A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of semiconductor technology, and in particular to a spectroscopic method for measuring the built-in electric field intensity on the surface of a gallium nitride crystal. Background Art
[0002] In semiconductor materials and devices, the built-in electric field is an important factor affecting their electronic and optical properties. The built-in electric field usually exists in pn junctions, heterojunctions, quantum wells, and material surfaces and interfaces, and is caused by uneven charge distribution or polarization effects. Accurately measuring and understanding the strength of the built-in electric field is crucial for regulating the electrical, optical, and thermal properties of semiconductor devices, especially in microelectronic and optoelectronic devices (such as field-effect transistors, diodes, light-emitting diodes, and solar cells). Gallium nitride (GaN) and its related materials (such as InGaN and AlGaN) are important wide-bandgap semiconductors that are widely used in the manufacture of high-power, high-frequency electronic devices and high-efficiency light-emitting devices (such as LEDs and lasers). GaN materials have strong spontaneous polarization and piezoelectric polarization effects, which lead to strong built-in electric fields inside and on the surface of the material. The built-in electric field has a significant impact on the carrier transport, band structure, and optical properties of GaN-based devices. Therefore, developing effective experimental methods to measure and study the built-in electric field on the GaN surface is of great significance for understanding and optimizing device performance.
[0003] Ultrafast transient reflection spectroscopy is an emerging optical measurement technology. This technology can perform non-contact dynamic measurement of the built-in electric field of semiconductor materials by irradiating samples with ultrashort pulse lasers (usually in the order of femtoseconds) and measuring the changes in the reflection spectrum in real time, providing a powerful means for studying the evolution of the electric field on the surface of semiconductors. To this end, the purpose of the present invention is to develop an ultrafast transient reflection spectroscopy method for measuring the intensity of the built-in electric field on the surface of gallium nitride crystals, which is used to study the intensity of the built-in electric field on the surface of gallium nitride crystals. Summary of the invention
[0004] The technical problem to be solved by the present invention is: to propose an ultrafast transient reflection spectroscopy method for measuring the built-in electric field strength on the surface of a gallium nitride crystal: using pump-probe technology, by changing the wavelength of the pump light to control the initial carrier concentration distribution, using the probe light to monitor the evolution of the reflectivity in real time, and fitting the carrier diffusion-drift coupling model to obtain the strength of the built-in electric field.
[0005] The technical solution adopted by the present invention to achieve the above-mentioned purpose is: a spectroscopic method for measuring the built-in electric field strength on the surface of a gallium nitride crystal, comprising the following steps:
[0006] The laser uses single-photon excitation or two-photon excitation to excite electrons to the conduction band, leaving holes in the valence band; white light is used as the detection light to detect the changes of excited state carriers in real time;
[0007] The incident angle of the detection light on the gallium nitride thin film sample is adjusted, and the pump light emitted by the optical parametric amplifier is incident on the front side of the gallium nitride thin film sample;
[0008] Collect the probe light reflected from the surface of the GaN film sample and test the transient absorption spectrum;
[0009] According to the spectral information, ΔR / R data is obtained; wherein R represents the reflectivity of the detection light with pump light excitation, and ΔR represents the difference between the reflectivity of the detection light with pump light excitation and the reflectivity of the detection light without pump light excitation;
[0010] According to the ΔR / R data, the depletion layer width is obtained by fitting; and the built-in electric field strength is obtained according to the depletion layer width.
[0011] The detection light wavelength covers 340nm to 800nm.
[0012] The incident angle of the detection light on the gallium nitride film sample is adjusted to 45°.
[0013] The pump light emitted by the optical parametric amplifier is incident on the front side of the gallium nitride film sample, with an incident angle of 0-10°.
[0014] The pump light excitation wavelength was changed to 260nm and 400nm to test the transient reflection spectrum.
[0015] The ΔR / R data is obtained, and the carrier drift-diffusion model is used to fit the experimental data to obtain the depletion layer width of the built-in electric field.
[0016] The built-in electric field strength is obtained according to the depletion layer width, which is obtained by the following formula:
[0017]
[0018] Where F is the built-in electric field strength, W 0 is the depletion layer width, q is the electron charge, N D is the doping concentration, ε is the relative dielectric constant, ε 0 is the dielectric constant of vacuum.
[0019] The present invention has the following beneficial effects and advantages:
[0020] 1. Transient reflectance spectroscopy is an optical method, so it can be measured without contacting the sample, avoiding the interference that may be introduced by electrode contact in traditional electrical methods. This non-contact measurement is particularly suitable for semiconductor materials with sensitive or easily damaged surfaces.
[0021] 2. Traditional electrical measurements sometimes require the preparation of electrodes on the sample or the introduction of an external electric field, which may have certain physical or chemical effects on the surface of the material. However, transient reflectance spectroscopy is completely non-invasive and will not damage the sample, making it particularly suitable for measuring fragile or difficult-to-handle materials.
[0022] 3. Using transient reflectance spectroscopy, spatial resolution of micrometers or even nanometers can be achieved through optical focusing, thereby measuring the built-in electric field in a local area of the semiconductor surface. In contrast, traditional electrical methods usually have difficulty achieving such high spatial resolution. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Optical path diagram of the ultrafast transient reflection spectrum constructed.
[0024] Figure 2 It is a transient reflection time-sharing spectrum diagram of GaN epitaxy in the embodiment.
[0025] Figure 3 Graph showing carrier dynamics of gallium nitride epitaxy under conditions of excitation at different excitation wavelengths in the embodiment.
[0026] Figure 4 The figure is a flow chart of the method of the present invention. DETAILED DESCRIPTION
[0027] The present invention is further described in detail below in conjunction with examples and drawings, but the embodiments of the present invention are not limited thereto.
[0028] The present invention discloses a spectroscopic method for measuring the built-in electric field strength on the surface of gallium nitride crystals. The carrier dynamics in the built-in electric field on the surface of gallium nitride crystals was studied by using femtosecond transient reflection spectroscopy technology, and the measurement of the built-in electric field strength on the surface was achieved, including the following steps: building a pump-probe transient reflection optical path, testing the transient reflection spectrum of the gallium nitride epitaxial surface, testing the evolution of the surface built-in electric field strength under different initial carrier distributions over time by changing different excitation wavelengths, obtaining the depletion layer thickness of the built-in electric field on the gallium nitride surface by fitting the carrier diffusion-drift coupling model, and calculating the strength of the built-in electric field. As an ultrafast time-resolved pump-probe spectroscopy technology, the present invention is suitable for studying the carrier dynamics on the surface of heavily doped gallium nitride, and provides theoretical guidance for optimizing the performance of GaN-based optoelectronic devices.
[0029] like Figure 4 Described, the present invention comprises the following steps:
[0030] (1) Construction of the optical path of femtosecond transient reflectance spectroscopy: This system mainly includes three components: femtosecond Ti:sapphire laser system (800nm, 35fs, 1kHz), optical parametric amplifier (OPA) and transient spectrometer. Among them, TOPAS OPA is mainly used to generate wavelength-adjustable pump light (240nm~2600nm); and the transient spectrometer includes a delay control device (Variable Delay), a calcium fluoride crystal window, a chopper and a detector. The system can achieve a time resolution of 35fs, a maximum delay time of 8ns, and the wavelength of the probe light (white light) can cover 340nm~800nm. Adjust the incident angle of the probe light on the thin film sample to about 45°, and the probe light reflected by the sample surface enters the fiber spectrometer; the pump light is incident on the front of the thin film sample with an incident angle of 0-10°.
[0031] (2) GaN epitaxial transient reflection spectrum test: The sample is a Si-doped (0001) crystal face GaN epitaxial wafer with a thickness of 4.5 microns. Single-photon excitation and two-photon excitation are used to excite electrons to the conduction band. The pump light wavelengths are 260nm and 400nm respectively, and the detection light wavelength range is 340nm-800nm. The detection light is collected by an ultraviolet detector to test the transient absorption spectrum.
[0032] (4) Calculation of GaN built-in electric field strength: On the semiconductor surface, carriers can drift, diffuse, and recombine. Drift and diffusion will lead to an enhancement of the modulated electric field ( Figure 3 The signal observed in the photoelectric field rises from 0 to -1), while carrier recombination will lead to a decrease in the photogenerated electric field (the signal observed decays from -1 to 0). It is assumed here that the carriers in the depletion region are mainly drifting, while the carriers outside the depletion region (neutral region) are mainly diffusing. The carriers residing in the neutral region can diffuse into the depletion region or diffuse into the bulk phase driven by the concentration gradient.
[0033] (5) Collect ΔR / R data, and use the carrier drift-diffusion coupling model to fit the experimentally collected data of ΔR / R changing with the delay time to obtain the depletion layer width. Where R represents the reflectivity of the probe light on the sample surface that is not excited by the pump light, and ΔR represents the difference between the reflectivity of the probe light with pump light excitation and the reflectivity of the probe light without pump light excitation.
[0034] The change of carrier concentration distribution in the neutral region of GaN film over time can be expressed as:
[0035]
[0036] Here, N represents the carrier concentration, D is the minority carrier (hole) diffusion coefficient, τ is the bulk recombination lifetime, t is the delay time after the sample is excited, and x is the depth from the sample surface.
[0037] For n-type doped GaN, there is an upward band bending on the surface. The photogenerated holes diffuse into the depletion layer, and then the holes are swept to the surface under the action of the built-in electric field; the photogenerated electrons are swept to the surface of the neutral region under the action of the built-in electric field, and then diffuse into the bulk phase. The final transient electric field strength depends on the number of photogenerated holes from the bulk phase to the depletion layer. A common approach is to assume that a virtual boundary surface separates the depletion region from the neutral region, and the carrier flux at the boundary is characterized by the charge carrier rate, resulting in the boundary conditions that the carrier flux needs to satisfy as shown below:
[0038]
[0039] Here, W 0 is the depletion layer width, S V is the hole thermal velocity at the virtual boundary of the depletion layer, and J represents the carrier flux. The final transient reflection signal is proportional to the carrier concentration, that is,
[0040]
[0041] Different excitation wavelengths have different absorption coefficients, so the initial carrier concentration distribution is also different. The initial carrier concentration distribution is expressed as
[0042] N(x, 0) = N 0 ·exp(-αx) (5)
[0043] Where α is the absorption coefficient, N 0 is the carrier concentration at time t = 0. Using the carrier drift-diffusion coupling model composed of formulas (1)-(5), the depletion layer width and the minority carrier (hole) diffusion coefficient D can be obtained by fitting the TR dynamics.
[0044] (6) Calculation of built-in electric field strength: The formula for built-in electric field strength is as follows:
[0045]
[0046] Where q is the electron charge, N D is the doping concentration, ε is the relative dielectric constant, ε 0 is the dielectric constant of vacuum.
[0047] Example:
[0048] This embodiment describes a method for measuring the built-in electric field strength on the surface of a GaN epitaxial layer, using a Si-doped GaN epitaxial layer with a (0001) crystal plane grown on a sapphire substrate as a demonstration object, and specifically includes the following steps:
[0049] 1. Build an ultrafast time-resolved transient reflectance spectroscopy optical path based on pump-probe technology. The details are in Figure 1 Displayed in.
[0050] The incident angle of the probe light on the GaN thin film sample is adjusted to about 45°; the angle of the reflector is adjusted so that the pump light is vertically incident on the surface of the GaN thin film sample, and the incident angle is 0°.
[0051] 2. The band gap of gallium nitride is 3.4eV, and 260nm is selected as the excitation light (photon energy is about 4.8ev). The valence band electrons are excited to the conduction band through single-photon excitation technology, leaving holes in the valence band; supercontinuum white light is used as the detection light to detect the changes of excited state carriers in real time. Figure 2 As shown, it is the time-sharing spectrum of GaN transient reflection spectrum. It can be seen that there is a spectral oscillation phenomenon above the band gap, which is the FKO oscillation caused by the built-in electric field.
[0052] 3. Use 260nm and 400nm as pump light respectively to extract the dynamics at 366nm, such as Figure 3 As shown. Using formulas (1), (2), (3), (4), and (5) to write a fitting program and fit the experimental data, it can be found that the experimental data and the fitting curve are completely consistent. Among them, the fixed first-order decay rate is 1E+9s -1 , GaN epitaxial thickness 2μm, Sv is 1E+7cm / s, surface recombination rate is 1000cm / s, the final fitting result: diffusion coefficient D is 0.466cm 2 / s, depletion layer thickness W 0 It is 31.0nm.
[0053] 4. Calculate the built-in electric field strength on the GaN surface according to formula (6), where q is 1.6*10 -19 C, W 0 31.0nm, N D 1*10 18 cm -3 , ε is 9.5, ε 0 8.85*10 -12 Substituting F / m into formula (6), we get the built-in electric field strength to be 3.1*10 4 V / cm.
Claims
1. A spectroscopic method for measuring the built-in electric field strength on the surface of a gallium nitride crystal, characterized in that: The following steps are involved: The electrons are excited to the conduction band by single-photon or two-photon excitation using a laser, leaving holes in the valence band; White light is used as the probe light to detect the changes of excited state carriers in real time; The incident angle of the detection light on the gallium nitride thin film sample is adjusted, and the pump light emitted by the optical parametric amplifier is incident on the front side of the gallium nitride thin film sample; Collect the probe light reflected from the surface of the GaN film sample and test the transient absorption spectrum; According to the spectral information, ΔR / R data is obtained; wherein R represents the reflectivity of the detection light with pump light excitation, and ΔR represents the difference between the reflectivity of the detection light with pump light excitation and the reflectivity of the detection light without pump light excitation; According to the ΔR / R data, the depletion layer width is obtained by fitting; and the built-in electric field strength is obtained according to the depletion layer width.
2. A spectroscopic method for measuring the built-in electric field strength on the surface of a gallium nitride crystal according to claim 1, characterized in that: The detection light wavelength covers 340nm to 800nm.
3. The spectroscopy method for measuring the built-in electric field strength on the surface of a gallium nitride crystal according to claim 1, characterized in that: The incident angle of the detection light on the gallium nitride film sample is adjusted to 45°.
4. The spectroscopy method for measuring the built-in electric field strength on the surface of a gallium nitride crystal according to claim 1, characterized in that: The pump light emitted by the optical parametric amplifier is incident on the front side of the gallium nitride film sample, with an incident angle of 0-10°.
5. The spectroscopy method for measuring the built-in electric field strength on the surface of gallium nitride crystal according to claim 1, characterized in that: The pump light excitation wavelength was changed to 260nm and 400nm to test the transient reflection spectrum.
6. The spectroscopic method for measuring the built-in electric field strength on the surface of a gallium nitride crystal according to claim 1, wherein the ΔR / R data is obtained, and the carrier drift-diffusion model is used to fit the experimental data to obtain the depletion layer width of the built-in electric field.
7. The spectroscopy method for measuring the built-in electric field strength on the surface of a gallium nitride crystal according to claim 1, wherein the built-in electric field strength is obtained according to the depletion layer width, and is obtained by the following formula: in, F is the built-in electric field strength, W0 is the depletion layer width, q is the electron charge, N D is the doping concentration, ε is the relative dielectric constant, and ε0 is the vacuum dielectric constant.
Citation Information
Patent Citations
Method for detecting unwanted interface charge of mercury cadmium telluride thin film photovoltaic device
CN101221203A
Method for measuring TR and longitudinal diffusion coefficient of thin film through back excitation-front detection
CN116263403A
Spectroscopic method for measuring electron or hole diffusion coefficient
CN117405608A
Method and device for modulating light by using semiconductor element of quantum well structure
JP1993173200A
Semiconductor crystal measuring method
JP1998199949A